The Islamic Context of the Thousand and One Nights: By Muhsin J. al-Musawi (New York: Columbia University Press, 2009. hbk. 352 pages) (American Journal of Islam and Society, 2011)
The Islamic Context of the Thousand and One Nights by Muhsin J. al-Musawicontains seven chapters, an introduction, and a conclusion. It addressesthe Islamic factor in global times, the unifying Islamic factor, the age ofthe Muslim empire, and the burgeoning of a text. It also examines the roleof the public, non-religious displacements in popular tradition, namely, theduality between Islam and culture—as well as the public role in narrativetheorizations, that is, the impact of literary criticism. Finally, the authorexplores Scheherazade’s nonverbal narratives in religious contexts, demonstratingthe underlying Islamic character of the work.Musawi’s recent work is a most welcome and long-needed additionto scholarship in the field of Arabic literature. Well-written and well-researchedby one of the senior scholars on the subject, The Islamic Contextdemonstrates how the Thousand and One Nights operate within the parametersof the Islamic faith. A portrait of life in all its aspects, the work wouldnever have reached us had it not been the product of a strong Islamic literaryand cultural climate. Although rife with erotic escapades, sexual sinsrarely go unpunished in the work. Despite all the morally deviant behaviordisplayed in the work, many of its tales are cautionary; they communicateethical messages and promote the good and forbid the wrong throughwarnings grounded in Islamic law. While there is no shortage of sex in amultiracial, multilingual, and multicultural society, much of the merrymakingis motivated by love, instead of lust ...